Peran Pendidikan Kewarganegaraan Dalam Meningkatkan Kesadaran Demokrasi Di Kalangan Remaja - Waskita, Dani (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
Citizenship Education (Civic Education) plays a significant role in shaping democracy awareness among adolescents. This study aims to analyze the impact of Citizenship Education on adolescents' understanding and participation in democracy. Using a descriptive quantitative approach with a survey of 120 high school students, the study found that the majority of students had a good understanding of democratic principles, although their involvement in socio-political activities outside of school remained low. Effective Citizenship Education, especially when based on discussions, simulations, and case studies, was found to enhance students' democracy awareness. However, challenges were found in the implementation of less varied methods and the negative influence of social media. The study recommends updating the Citizenship Education curriculum and strengthening digital media literacy to improve democracy awareness among adolescents.